Animal experiments data: Structural analysis and design a model for determining lethal drug dosage - BABANLI, A; GUNES, A (The Indian Journal of Animal Sciences, 2013)
The ACD-IDEA database, originally developed by the authors, stores main results of scientific publications on animal experiments realized around the world during the last 100 years. In this paper a common statistical analysis of this database is presented. On the basis of the knowledge extracted from this database, a rule-based model is developed that is able to estimate lethal drug dosages for a given groups of compounds and animals. A decision tree is designed and a set of association rules with exceptions is created. This model can be used for determining lethal dosage values for drugs of the category â€œGeneral anesthetic compoundsâ€ and for animals of the group â€œrabbit, cat, dog, guinea pigâ€. This model can also be used in a diverse set of problems of pharmacological research and education.